Synthetic Access to Fluorocyclopropylidenes - Melngaile, Renate; Videja, Melita; Kuka, Janis; Kinens, Artis; Zacs, Dzintars; Veliks, Janis (Organic letters, 2023)
Herein we report an approach for the straightforward preparation of fluorocyclopropylidene group from aldehydes and ketones via Julia- Kocienski olefination using the newly developed reagent 5-((2-fluorocyclo-propyl)sulfonyl)-1-phenyl-1H-tetrazole. Derivatization of monofluorocyclopro-pylidene compounds includes hydrogenation to deliver fluorocyclopropylmethyl compounds and fluorinated cyclobutanones. The utility of the described method is demonstrated by the synthesis of a fluorocyclopropyl-containing analogue of ibuprofen. Bioisosteric replacement of isobutyl with the fluorocyclopropyl group may be used for tuning biological properties of drug molecules.